2018
DOI: 10.1111/dme.13830
|View full text |Cite
|
Sign up to set email alerts
|

Physical symptom complaints, cognitive emotion regulation strategies, self‐compassion and diabetes distress among adults with Type 2 diabetes

Abstract: Aims Diabetes‐related distress is common among adults with Type 2 diabetes and is consistently associated with poorer self‐management and treatment outcomes. However, little is known about the psychological factors that may contribute to or protect against diabetes distress. This study examined illness burden, and positive and negative ways of thinking and relating to oneself in times of stress, as independent correlates of diabetes distress, cross sectionally and longitudinally. Method A total of 120 adults t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
2
23
0
3
Order By: Relevance
“…As such, we cannot be certain about the directions of the relationship between self-compassion, self-coldness, and life satisfaction. However, we prepared our model based on experimental and correlational findings indicating that selfcompassion exerts a positive influence on life satisfaction and well-being, whereas self-coldness predicts depression and anxiety (Eriksson et al 2018;Kane et al 2018). To infer causality, future studies should examine our study model longitudinally.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we cannot be certain about the directions of the relationship between self-compassion, self-coldness, and life satisfaction. However, we prepared our model based on experimental and correlational findings indicating that selfcompassion exerts a positive influence on life satisfaction and well-being, whereas self-coldness predicts depression and anxiety (Eriksson et al 2018;Kane et al 2018). To infer causality, future studies should examine our study model longitudinally.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…A growing number of studies have demonstrated that the three positive scales and three negative scales of the SCS in fact create two separate, superordinate factors (named selfcompassion and self-coldness or self-criticism, respectively; Brenner et al 2017;López et al 2015) that are theoretically distinct, have unique associations with well-being and distress, and respond differently to interventions (Brenner et al 2018;Eriksson et al 2018). In diabetes research, one study considered the distinction between self-compassion and selfcoldness (Kane et al 2018); in a sample of adults with T2D, baseline self-coldness significantly predicted diabetes distress over 3 months. By contrast, self-compassion was not independently correlated with diabetes distress, neither crosssectionally nor longitudinally (Kane et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Fourth, self-compassion is strongly related to compassion for others. 23,31 Therefore, self-compassion could play a protective and facilitative role when using process recording, which has a potential risk of negative effects such as inducing excessive rumination; its use should therefore be considered and enhanced in nursing education.…”
mentioning
confidence: 99%
“…Kane et al . have highlighted the high rates of diabetes distress in people with Type 2 diabetes, linking distress with more self‐criticism and ‐judgement as well as with physical symptoms. There seems no doubt that greater attention is needed to identify psychological morbidity in people with diabetes and Rauwerda et al .…”
mentioning
confidence: 99%